Risk of caries adjacent to different restoration materials: Systematic review of in situ studies. (January 2017) - Askar, Haitham; Tu, Yu-Kang; Paris, Sebastian; Yeh, Yi-Chun; Schwendicke, Falk
Abstract: Objectives: The risk of 'caries adjacent to restorations' (CAR) might depend on the used restorative materials. In situ studies are often used to compare the risk of caries adjacent to different materials. We aimed to review in situ studies to evaluate how different materials contribute to risk of CAR. Data sources: We included in situ controlled trials comparing directly placed restorative materials, reporting on caries (mineral loss, measured via radiography or micro-hardness) adjacent to these materials. Medline, Embase and Cochrane CENTRAL were systematically searched. Screening and data extraction was performed independently by two authors. Materials were classified according to the used adhesive and restorative materials. Fixed-effects pairwise and frequentistic network meta-analyses were performed Study selection: Nine studies (132 patients, 8 materials) were included, yielding inconsistent results. We could not identify underlying reasons, as confounders were only limitedly reported. The resulting material rankings come with great uncertainty, and raise doubts as to the validity and transferability of in situ studies as well as the applicability of their findings. Conclusions: The current body of evidence of in situ studies is insufficient for firm conclusions as to the caries risk adjacent to different materials. The validity and applicability of included studies remain uncertain. Clinical significance: While single in situ studies seem to convey consistent and applicable information, the overall body of evidence is inconsistent, limiting the conclusions which can be drawn from it.